Taking Account of Both Languages in the Assessment of Dual Language Learners - de Villiers, Jill (Seminars in Speech and Language, 2015)
This article addresses the issue of “adjusted” assessment of bilingual children, a practice that acknowledges that children who know two languages have distributed knowledge of those languages. In recent work, at least three procedures have become common for taking into account this distributed knowledge: a conceptual score, in which children are given credit for knowing some feature of language in either language; a combined or total score, which adds units of knowledge from each language together; and a best score, in which the performance in the better language is taken as the most appropriate measure. The article begins with a discussion of the rationale behind the varied scores. After reviewing a sample of studies that used each type, I will argue that vocabulary and morphosyntax are fundamentally different types of knowledge that may need distinct kinds of adjusted measurement. The value of each kind of adjusted assessment must be considered relative to its purpose: is it to gauge the child's readiness for schooling? Or is it to detect language disorders? Finally, a plea is made for more basic research to answer the many questions that are raised.
Keywords: Dual language learners; Spanish-English bilinguals; distributed knowledge; conceptual score; total score; best score; transfer and assessment